Adaptation and Mitigation Model for People to Restore Their Ecosystem from Flood in Semarang, Indonesia - Muzakar Isa; FX. Sugiyanto; Indah Susilowati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
The northern coast of Central Java province is considered as the critical area of flood path. Semarang as capital city of this province with its junction area of Kendal and Demak always suffering from flood due to rain and or high tide seawater. It is realised that infrastructures’ capacity for flood control, awareness of people and other multi-factors are significantly contributed on the flood problem in these area. Mixed-methods of quantitative and qualitative are employed to analyze the data. The study found that there was a decline in quality of - people’s life, environment and its ecosystem. Awareness and responsiveness of people and also the other stakeholders are not progressive to overcome the problem of flood. This study is trying to contribute in outlining a model of adaptation and mitigation for the people to restore their ecosystem from the perspective of economist.